Site-specific ground response analysis at a site in the affected area of the 2016 Pidie Jaya earthquake - H., Yunita; N., Al Huda; T., Saidi; A., Yuliannur; B., Setiawan; Putra Jaya, Ramadhansyah; Mohamad Idris, Ali (IOP Publishing, 2020)
Analytical models have demonstrated that they are able to simulate reasonably well the seismic motions at the ground level. The most widely used model is the equivalent linear approach. This equivalent linear model was used to compute the free-field response of Meureudu-Pidie Jaya, Aceh Indonesia's soft soils during the 2016 Pidie Jaya earthquake. The model computes the ground response of horizontally layered soil deposits subjected to transient and vertically propagating shear waves through the one-dimensional soil column. Each soil layer is assumed to be homogeneous, visco-elastic and infinite in the horizontal extent. The equivalent linear estimation of soil properties is taken to express the nonlinearity of the soil's shear modulus and damping values. These values are assumed to be a function of shear strain amplitude and determined by an iterative process that must be consistent with the level of the effective strain induced in each sub-layer. Starting with the highest shear modulus and a low damping value, the shear modulus and the damping ratio of each sub-layer are modified. The modification is based on the applicable relationship between both properties and the shear strain. The calculation is repeated until strain-compatible modulus and damping values converge within a tolerance of 1%. This research reveals the ground motions of Pidie Jaya's soils. The results of the analysis are presented.